2020
DOI: 10.7759/cureus.11169
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B12 Supplementation: Preventing Onset and Improving Prognosis of Depression

Abstract: Depression is a common mental health condition occurring across all ages, genders, and populations and is almost always multifaceted. It can manifest as a form of metabolic disorder, endocrine disorder, cardiovascular diseases, inflammatory disorders, deficiencies, or neurodegenerative disorders. Although there have been various treatment options available for the treatment of depression, it is still a sizable global health concern requiring more attention. This review article was produced by researching data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 31 publications
(30 reference statements)
0
31
0
4
Order By: Relevance
“…The range of effects associated with VitB12 deficiency is very wide and often unrecognized and includes both mild symptoms (weakness, loss of appetite, and weight), and severe ones such as megaloblastic anemia, fertility, embryo development, cancer, and neurological modifications (e.g., numbness and tingling in limbs, depression, confusion, dementia, and optic neuropathy) [ 6 , 16 , 17 ]. In addition, VitB12 is involved in Peripheral Neuropathic Pain and supplementation can contribute to pain relief [ 18 ].…”
Section: Impact Of Vitb12 and Human Healthmentioning
confidence: 99%
“…The range of effects associated with VitB12 deficiency is very wide and often unrecognized and includes both mild symptoms (weakness, loss of appetite, and weight), and severe ones such as megaloblastic anemia, fertility, embryo development, cancer, and neurological modifications (e.g., numbness and tingling in limbs, depression, confusion, dementia, and optic neuropathy) [ 6 , 16 , 17 ]. In addition, VitB12 is involved in Peripheral Neuropathic Pain and supplementation can contribute to pain relief [ 18 ].…”
Section: Impact Of Vitb12 and Human Healthmentioning
confidence: 99%
“…A recent systematic review concluded that deficiency of vitamin B12 is associated with a higher risk of developing depression; however, it did not find any evidence of improvement in depressive symptoms by administration of vitamin B12 [ 18 ]. There are case reports of acute psychosis as a symptom of vitamin B12 deficiency as well as of acute onset of mania and gait disorder that responded well to vitamin B12 therapy [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moore et al (2012) reviewed 43 studies and revealed that B12 subclinical levels (<250 pmol/L) are associated with Alzheimer's disease, vascular dementia and Parkinson's disease, whilst there is a small subset of dementias that are reversible with vitamin B12 administration, however this therapy does not improve cognition in patients without preexisting deficiency 8 . Finally, due to the role of vitamin B12 in the nervous system, Sangle et al (2020) suggested that the lower levels of vitamin B12 are associated with a higher risk of developing depression 9 . All these, suggest a strong correlation between low B12 levels and frailty.…”
Section: Investigating the B12-frailty Interplaymentioning
confidence: 99%
“…Vitamin B12 deficiency is well known for its direct effects, such as megaloblastic anemia and subacute combined degeneration affecting spinal cord and peripheral nerves, dementia, etc[ 1 ]. Moreover, deficiency of B12 or low levels, may be a risk factor for other clinical manifestations such as fatigue, weakness, constipation, balance disorder, mental fogginess, peripheral tingling, depression, cognitive disorders, hematological, neurological and psychiatric disorders, coronary artery disease, or even autoimmune damage that may lead to hypothyroidism, type I diabetes mellitus, vitiligo[ 1 , 2 , 9 ]. Vitamin B12 deficiency is also responsible for causing many cases of mental disorders[ 9 ].…”
Section: B12 Vitamin Profilementioning
confidence: 99%
See 1 more Smart Citation